Missed opportunities for earlier diagnosis of HIV in patients who presented with advanced HIV disease: a retrospective cohort study - Levy, Itzchak (BMJ Open, 2016)
OBJECTIVE: To quantify and characterise missed opportunities for earlier HIV diagnosis in patients diagnosed with advanced HIV. DESIGN: A retrospective observational cohort study. SETTING: A central tertiary medical centre in Israel. MEASURES: The proportion of patients with advanced HIV, the proportion of missed opportunities to diagnose them earlier, and the rate of clinical indicator diseases (CIDs) in those patients. RESULTS: Between 2010 and 2015, 356 patients were diagnosed with HIV, 118 (33.4%) were diagnosed late, 57 (16%) with advanced HIV disease. Old age (OR=1.45 (95% CI 1.16 to 1.74)) and being heterosexual (OR=2.65 (95% CI 1.21 to 5.78)) were significant risk factors for being diagnosed late. All patients with advanced disease had at least one CID that did not lead to an HIV test in the 5 years prior to AIDS diagnosis. The median time between CID and AIDS diagnosis was 24 months (IQR 10–30). 60% of CIDs were missed by a general practitioner and 40% by a specialist. CONCLUSIONS: Missed opportunities to early diagnosis of HIV occur in primary and secondary care. Lack of national guidelines, lack of knowledge regarding CIDs and communication barriers with patients may contribute to a late diagnosis of HIV.